Tales from Kentucky Lawyers. - Montell, William (University Press of Kentucky, 2010)
""A woman was sitting on the witness stand, and the lawyer asked her, 'Did you, or did you not, on the night of June 23rd have sex with a hippie on the back of a motorcycle in a peach orchard?' She thought for a few minutes, then said, 'What was that date again?'"--The book Lawyers have long been known as master storytellers, and those from Kentucky are certainly no exception. Veteran oral historian and folklorist Lynwood Montell has collected tales from dozens of lawyers and judges from throughout the Bluegrass State, ranging from the story about the tough Jackson County judge who fined